Comparison of some morphological and absorption properties of the nanoparticles Au/TiO2 embedded films prepared by different technologies on the substrates for application in the plasmonic solar cell. (14th January 2015) - Dao, Khac An; Nguyen, Thi Thuy; Nguyen, Thi Mai Huong; Nguyen, Duy Thien
Abstract: The nanoparticle Au/TiO2 embedded system plays a very important role in the plasmonic solar cell. The features of the nanoparticle embedded system will determine light enhancement, light absorption, scattering and localized surface plasmon resonance (LSPR), aiming to enhance the efficiency of the plasmatic solar cell. The characterizations of nanoparticles Au/TiO2 embedded system consist of many parameters: the sizes of nanoparticles (Au, TiO2 ), the weight ratio of Au to TiO2, the thickness of the single layer or multilayer of Au/TiO2, the arrangements of Au and TiO2 nanoparticles in integrated-matrix system, the light absorption, scattering and LSPR capacities of the Au/TiO2 system. These parameters, however, depend on the technological conditions, the structure of plasmonic solar cell as well as the used substrate materials. This paper presents some technological developments for nanoparticles Au/TiO2 embedded systems by different methods, including the preparation of the mixer Au/TiO2 solutions and fabrication of the nanoparticle Au/TiO2 systems with different Au percentages on several substrates (glass/ITO and AAO(Al)/Si…), and measured results of the morphological, structural and optical properties using FESEM, EDX, UV–vis spectroscopy. The comparisons of experiment results between different technology conditions and substrates (glass/ITO, AAO(Al)/Si…) are also shown and discussed with the aim of choosing the suitable technological process and technological conditions for application in the plasmonic solar cell.